Analisis Peranan Dan Tugas Staff Komisi C Dalam Mendukung Kinerja Dewan Komisi C DPRD Provinsi Sumatera Utara - Friska Fauziah Umardhi; Muhammad Ikhsan Harahap (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Every student at the university must complete an internship, especially at the Islamic State University of North Sumatra. Every student must have practical work experience to be able to start working after college. Internships are a good way to align theoretical knowledge with the real world of work because basically the theoretic knowledge learned in the classroom is not necessarily the same as what is done in the field. Working practices provide a great opportunity for students to interact directly with the world of business or work. Problems can arise from the failure to strike a balance between something intended and a situation that corresponds to the facts, which leads to the question "why" or "what's the reason for this". In addition, problems can emerge as a result of doubts or invalid information about an object in depth. That's the purpose of this research. This research is carried out through a qualitative approach. The research will be conducted from January 16th to February 16th at the People's Representative Council of the North Sumatra Provincial Region (Dprd Provsu), located at Imam Bonjol No.5, Petisah Central, Medan Petisha District, Medan City, North Sumatera. The research found that the DPRD C Commission of North Sumatra Province is responsible for overseeing the budget, development programmes, public policies, local financial management, and organizational performance. Therefore, the evaluation of the implementation of core tasks and functions of the Commission C should cover several important aspects, such as transparency and accountability, the effectiveness of oversight and budget management, impact on economic growth, and so on.